TUBA1B as a novel prognostic biomarker correlated with immunosuppressive tumor microenvironment and immunotherapy response - Qi, Juntao; Zhou, Mingming; Yang, Na; Ma, Huiyun; He, Min; Wu, Gujie; Ge, Chang; Jin, Liuyin; Cheng, Lin; Liao, Wei; Ren, Hefei; Lei, Caiyun (Frontiers in Pharmacology, 2025)
Background: Tubulin alpha 1b (TUBA1B) is a key microtubule protein essential for maintaining cellular structure and function. This protein contributes significantly to cytoskeletal formation and is implicated in various diseases. Despite its fundamental roles, TUBA1B’s impact on tumor prognosis and the tumor immune microenvironment across cancer types remains inadequately understood.Methods To elucidate TUBA1B’s role in cancer prognosis and immune response, we conducted a comprehensive analysis, integrating data from established databases such as The Cancer Genome Atlas, Genotype Tissue Expression, Cancer Cell Lineage Encyclopedia, Human Protein Atlas, Kaplan-Meier Plotter, cBioPortal, TIMER, and ImmuCellAI, along with a large-scale clinical study and immunotherapy cohort. We also conducted in vitro functional assays to assess TUBA1B’s functional role in tumor cells, allowing for a detailed examination of its relationship with cancer prognosis and immune modulation.Results: Our findings indicate that TUBA1B expression is dysregulated across multiple cancers, correlating strongly with poor survival outcomes and advanced pathological stages. Functional enrichment analyses further revealed that TUBA1B regulates key cell cycle processes, driving tumor proliferation, migration, and invasion. It also influences immune functions within both the innate and adaptive immune systems, affecting immune-related signaling pathways. These insights underscore TUBA1B’s multifaceted role in cancer progression and immune response.Conclusion: This study highlights TUBA1B’s potential as a human oncogene with substantial roles in tumorigenesis and immune regulation. Elevated TUBA1B levels are associated with an immunosuppressive tumor microenvironment, impacting cancer progression and treatment outcomes. Targeting TUBA1B may offer promising therapeutic avenues for enhancing cancer treatment, offering new perspectives for innovative anti-tumor strategies with high clinical impact.